Helga Magnúsdóttir and Literacy Practices of Elite Widows in Seventeenth-century Iceland - Parson, Katelin Marit (Studier i Nordisk, 2026)
Little research exists on widowhood in early modern Icelandic society or the role of elite, property-owning widows. This article focuses on Helga Magnúsdóttir (1623-1677), an Icelandic woman who lived most of her adult life as a widow following the sudden death of her husband, sýslumaður Hákon Gíslason (1614-1652), after thirteen years of marriage. She was a cousin and close friend of Bishop Brynjólfur Sveinsson of Skálholt (1605-1675) and the owner of an important collection of books and manuscripts. Several documents provide insight into her literacy practices, examined here in the context of her widowhood. Marriage alliances were an important tool for individuals and kinship networks to maintain their elite identity in seventeenth-century Iceland, and examination of Helga’s kinship network indicates that remarriage was uncommon. Helga’s case gives insight into how elite widows managed the rapid transformation of their identity and suggests that literacy was central to widows’ ability to act as their late husbands’ representatives and take an active and assertive role within their communities and kin groups.